Faktor Eksternal yang Mempengaruhi Keterlambatan Proyek Konstruksi Gedung di Kota Padang - Ade Anggrainy; Wardi Wardi; Zaitul Zaitul (Jurnal Talenta Sipil, 2026)
Delays in building construction projects are a common problem that can lead to cost overruns and reduced project performance. This study aims to identify and determine the influence level of external factors on delays in building construction projects in Padang City, Indonesia. A quantitative research method was employed by collecting data through questionnaires distributed to 93 respondents, including contractors, consultants, and other related stakeholders. Data analysis was conducted using the Relative Importance Index (RII) method to assess the significance of each factor, and the Analytical Hierarchy Process (AHP) supported by Expert Choice software to determine the priority of dominant factors. The results indicate that socio-cultural factors, weather conditions, and delays in the permitting process are the most influential external factors contributing to project delays in Padang City. The findings of this study are expected to provide useful insights for stakeholders in improving project planning and control to reduce the risk of delays.